Studi Kasus Break Even Point Pada UMKM Seblak Ceu Yani - Pudholi, Ahmad; Setiyawan; Purba, Nur Annisa Failasuffaiza; Utami, Nurharini Budi; Fachrizal, Muhammad; Nabila, Salsa Is; Apriliyanto, Wahid Hidayah; Purnamasari, Dita; Anjellina, Yessyta Novi; Iswahyudi , Andre (Innovative: Journal Of Social Science Research, 2025)
Seblak Ceu Yani, a culinary business located in South Cikarang, Bekasi, was founded by Mrs. Yani and her two children in April 2022. Carrying the traditional Sundanese dish, seblak, this business offers a "buffet" concept with a variety of topping choices. Seblak Ceu Yani has succeeded in attracting customers because of its authentic taste and friendly service, especially for local people who like spicy food. However, like other small businesses, understanding financial health and business sustainability is very important for long-term success. This study aims to analyze the Break Even Point (BEP) of Seblak Ceu Yani to help business owners understand the amount of sales needed to cover fixed and variable costs, and to know the point at which the business starts to generate profits. The case study method proposed by Robert K. Yin (2003) was used in this study, with data collection from primary sources through interviews with Mrs. Yani, as well as secondary data related to financial theory and business management. The method used to calculate BEP is the unit contribution method, as explained by William J. Stevenson (2005), which involves calculating the contribution margin and dividing it by the selling price per serving. This study provides a detailed analysis of the costs involved and determines how many servings of seblak must be sold to reach the break-even point, as well as the sales target needed to achieve profit. The results of this study are expected to help Mrs. Yani in developing pricing strategies, managing costs, and setting realistic sales targets so that this business remains profitable. In addition, this analysis highlights the importance of financial planning and performance monitoring in small and medium enterprises (SMEs), as emphasized by Kotler and Keller (2016) and Hilton and Platt (2013). This study contributes to a deeper understanding of financial management in the context of the culinary business and the practical application of BEP analysis to ensure business sustainability.